Utility and Comparative Study of Chemical Review Journals (Documentation Problems. 19) - Singh, Mohinder (Journal of Information and Knowledge, 1979)
Scientific review journals play an important role in screening the relevant pieces of information from the overwhelming mass of literature and in keeping the scientific communities abreast about the significant progresses being made in research and development from time to time. Here, the paper embodies the comparative study of the physical characteristics of three chemical review journals, namely-Chemical Reviews, Chemical Society Reviews and Russian Chemical Reviews. While analysing the varying physical features of reviews, in association with it, the utilities of the same have also been discussed.